(untitled) (diségno, 2022)
"Drawing is not an autonomous reality. It is not: neither as an action nor as the result of an action. What makes drawing a heteronomous reality is its submission to that which is not drawing [Maldonado 1967, p. 217, redactional translation]. The play on words proposed by Vanni Pasca [2010] and, not surprisingly, used as the incipit of the call of this issue of the journal diségno, should be taken very seriously: the relationship between drawing and design as an element for triggering a broader reflection on the two disciplines and their theoretical and practical-operational foundations. [read more]